2004
DOI: 10.1021/jf035145e
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Functional Properties of the Essential Oil of Amazonian Basil, Ocimum micranthum Willd., Labiatae in Comparison with Commercial Essential Oils

Abstract: Wild Amazonian basil Ocimum micranthum Willd. (O. campechianum Mill.) Labiatae essential oil was analyzed by GC and GC-MS: 31 compounds were identified. The main components were eugenol (46.55 +/- 5.11%), beta-caryophyllene (11.94 +/- 1.31%), and beta-elemene (9.06 +/- 0.99%), while a small amount of linalool (1.49 +/- 0.16%) was detected. The oil was tested for its in vitro food-related biological activities and compared with common basil Ocimum basilicum and Thymus vulgaris commercial essential oils. Radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 24 publications
6
53
0
3
Order By: Relevance
“…Several methods are used for the estimation of efficiency of synthetic/natural antioxidants, like the 2, 2′-azobis(2-amidinopropane) dihydrochloride (AAPH)/linoleic acid assay 24 , 1,1-diphenyl-1-picrylhydrazyl (DPPH) assay [25][26][27][28][29] . The antioxidant activity of the 12 iridoids has been evaluated in both in vitro tests.…”
Section: Interaction With 11-diphenyl-picrylhydrazyl (Dpph) Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods are used for the estimation of efficiency of synthetic/natural antioxidants, like the 2, 2′-azobis(2-amidinopropane) dihydrochloride (AAPH)/linoleic acid assay 24 , 1,1-diphenyl-1-picrylhydrazyl (DPPH) assay [25][26][27][28][29] . The antioxidant activity of the 12 iridoids has been evaluated in both in vitro tests.…”
Section: Interaction With 11-diphenyl-picrylhydrazyl (Dpph) Activitymentioning
confidence: 99%
“…In literature, many studies concerning the antioxidant activity of natural substances tested with DPPH have been reported [25][26][27][28][29] .…”
Section: Interaction With 11-diphenyl-picrylhydrazyl (Dpph) Activitymentioning
confidence: 99%
“…Tsimidou and Boskou (1994) observed that between the herbs and spices extensively studied, the plants belonging to the Lamiaceae family have significant antioxidant activity. In spite of the intensive investigation of the antioxidant activities of the European and Asian herbs and spices, little is known about the properties of these plants in South America (Stashenko et al, 2004;Sachettii et al, 2004;Costa et al, 2008;Sousa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Within this family, the genus Ocimum provides various species, and Ocimum basilicum is one of the more than 60 Ocimum species. These Ocimum plants, plant parts, extracts and essential oils are used as spices and flavours for various food products as well as effective drugs for many applications in folk medicine especially in Africa and Asia (Sacchetti et al, 2004;Jirovetz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%